Jack’s Multiple Personality in Marrowbone Film - Prafitri, Wilma; Rahayu, Famala Eka Sanhadi; Ary Ivanka (The Study Program of English Education of Palangka Raya University, 2024)
This study examined the manifestation of Jack's multiple personality in the film Marrowbone. The film